Isolation of biotechnologically important enzyme producing Rhizobacteria from seasonal flower beds (Dhaka University Journal of Biological Sciences, 2023)
This study aimed to isolate biotechnologically important enzyme like amylase and protease producing rhizobacteria from rhizospheric soil. Soil samples were collected from the rhizospherc of five different flowering plants from Curzon hall, University of Dhaka. A good number of bacteria were isolated. Among them 12 bacterial isolates were selected for detailed study based on their amylolytic and proteolytic activity. Starch hydrolysis ratio (SHR) of the studied isolates ranged in between 2.06 and 4.67, casein hydrolysis ratio (CHR) ranged in between 2.27 and 3.92. All the selected isolateswere Gram positive and rod shaped and provisionally identified as the member of the genus Bacillus with five different species viz. Bacillus alcalophilus, B. subtilis, B. pumilus, B. firmus and B. lentus. Amylase and protease production of the studied bacteria were estimated and it was ranged in between 29.11±9.57 to 35.78 ± 9.05 and 230.27±37.08 to 276.47 ± 55.01 U/ml. The highest amylase and protease producer were Bacillus alcalophilus (Ce104/S9/L) which could produce 35.78 ± 9.05 U/ml and Bacillus subtilis (Ca71/S5/L) could produce 276.47 ± 55.01 U/ml of protease, respectively. Maximum production of both amylase and protease was achieved in 24 h of incubation period at 37°C and pH 7.0.Dhaka Univ. J. Biol. Sci. 32(1): 65-71, 2023 (January)